Immunomodulatory Effects of Rhaphidophora Korthalsii Methanol Extract on Natural Killer Cell Activation and Cytolytic Activity - Yeap, Swee Keong (2010)
Rhaphidophora korthalsii (Araceae) is a root-climber plant which has been previously identified as splenocyte immunostimulator. The purpose of this study was to examine the in vitro and in vivo immunomodulatory effect of R. korthalsii methanol extract on immune cell proliferation, cytokine expression and cytotoxicity. More specifically, immunomodulatory effects of R. korthalsii methanol extract on the stimulation of NK cells activity and cytotoxicity against HepG2 monolayer and spheroid culture were determined. Immune cells [peripheral blood mononuclear cells (PBMC) and mice splenocytes] treated with this extract resulted in stimulation of cell proliferation, cytokine expression and cytotoxicity in dose and time dependent manner. For the in vivo immunostimulatory effect study, unlike rIL-2 which degraded rapidly, the stimulatory effect from the extract managed to last until day 15. In order to understand the activation of NK cells by R. korthalsii methanol extract, NK cells were treated directly or indirectly. Both direct and indirect stimulated NK cells showed high-level expression of cell surface FasL, NKG2D, 16B4 and extra-cellular IFN-γ and TNF-α. These activations contributed to the killing of NK cells against HepG2 monolayer cells through Granzyme B mitochondria caspases dependent secretory apoptosis pathway where DNA fragmentation, phosphatidylserine (PS) externalisation, caspase 3, caspase 8, caspase 9 up-regulation and XIAP, Bid downregulation were observed. Apart from that, extract stimulated NK cells which caused cell death on the HepG2 spheroid and inhibited the HepG2 cell invasion, suggesting that R. korthalsii methanol extract was a potential agent to inhibit liver tumour metastasis. Our findings indicated a potential IL-2 free immunotherapy through direct and indirect R. korthalsii activation on NK cells which can further induce apoptosis on the HepG2 monolayer and spheroid culture.